Wine Tourism and Sustainability – A Case Study - Nave, Ana Cláudia Pinto; Paço, Arminda Maria Finisterra (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2019)
The wine tourism industry has a significant contribution to Portugal’s socio-economic development. Considering the importance of sustainability for the wine tourism sector, companies are increasingly starting to set goals and objectives based on sustainable development. This study aims to present the case study of a large Portuguese company, describing the way these organisations promote sustainability in the sector of wine tourism. The qualitative research method adopted was based in documentary analysis. Content analysis revealed that the mechanisms used to promote and implement sustainable practices were recognised by the community. In the practical domain, the study can stimulate companies to implement practices in order to promote sustainability and also to contribute to adding value to tourism associated with wine.